The Retention and Fracture Resistance of Two All-ceramic Post and Core Systems in Anterior Endodontically Treated Teeth: - Shafiee, Zeinab; Rahmani, Naeeme; Safari, Anahita; Khaledi, Amir Alireza (Galen Medical Journal, 2014)
Background: In anterior endodontically treated teeth a better esthetic can be achieved by using all-ceramic post -core restorations instead of metal post systems. Maximum retention and fracture resistance of the post are the criteria upon which selection of a post system is based. The aim of this study was to evaluate the fracture resistance and retention of two all-ceramic post and core systems including IPS Empress 2 post-core system and IPS Empress 2 core connected to Zirconium Cosmopost, and comparing these features among the two groups Material and methods: Eighty extracted maxillary central incisors and canines were divided into two groups of 40 including IPS Empress 2 and zirconium Cosmopost. To evaluate retention, shear force was applied to the cement at the crosshead speed of 0.5 mm/min; force was applied until the post was detached from the canal. To measure the fracture resistance, the samples were loaded at 45-degrees to the horizon at the crosshead speed of 5 mm/min until fracture occurred. Result: The mean fracture strength and standard deviation of zirconium Cosmopost and IPS Empress 2 were 302.10 N (69.922), 151.63 N (48.661), respectively. The difference between groups was significant statistically (P<0.001). The zirconium Cosmoposts had lower retention than IPS Empress2 dowel-core, but the difference between groups was insignificant (p =0.134). Conclusion: Within the limitations of the study, it could be concluded that zirconium Cosmopost system may be a candidate for the restoration of anterior endodontically treated teeth, as the high fracture toughness and propitious esthetic feature.